Language Disorder of the Main Character in Dancing in the Rain Movie - Rosyida Ekawati; Zakiyatul Arofat (Talenta Publisher, 2022)
This study is aimed at finding out types of language disorder and explaining the symptoms shown in each type of language disorders experienced by the main character in “Dancing in the Rain” movie. This study uses descriptive qualitative method. The data of this study are in the form of words, phrases, sentences and behavior which taken from the main character’s utterances and behaviors during his engagement in activities. The result of this study shows that the two types of language disorder: expressive language disorder and receptive language disorder were experienced by Banyu Anggoro as the main character in ‘Dancing in the Rain’ movie. Each type of language disoder shows some different symptoms with varying occurrences. The symptoms shown in receptive language disorder are not appearing to listen, difficulty following verbal directions, limited vocabulary, difficulty understanding complex sentences, difficulty interpreting words or phrases, and demonstrating lack of interest. Meanwhile, the symptoms of expressive language disorder are word-finding difficulties, limited vocabulary, over reliance on stock phrases, and difficulty coming to the point of what they are trying to say.